Optimised operation of integrated community energy system considering integrated energy pricing strategy: A two-layer Stackelberg game approach - Yang, Dongfeng; He, Ziqian; Sun, Yong; Li, Baoju; Li, DeXin; Liu, Xiaojun; Jiang, Chao (Journal of energy storage, 2024)
Aiming at the problems of new energy absorption and inter-subject interest conflict in the integrated community energy system, this study proposed an integrated energy pricing strategy that considered the interconversion of various energy sources and built a two-layer optimisation model of the electric-gas-heat‑hydrogen interconnection integrated community energy system. The upper-layer operator model maximises the revenue by setting energy price and selling energy to users. The lower-layer users model minimises the energy cost by actively adjusting energy usage strategy according to energy price. The two sides rationally pursue the maximisation of their respective interests, and the process of bargaining can be described by Stackelberg game. The model is also considered for combining the characteristics of elastic load and vehicle-to-grid on the demand side and operates jointly with the bus battery swapping station and two-stage power-to-gas for optimizing system operation. Through theoretical derivation, it is proved that there is a unique Stackelberg equilibrium solution for the proposed game model. Further, the two-layer optimisation model is transformed into a mixed integer quadratic programming problem by applying the Karush-Kuhn-Tucher optimal condition, linear relaxation technique, and duality theorem. Finally, the global optimal energy price is obtained by solving the converted model. The optimisation results in different scenarios show that the proposed model and method not only protect the interests of the operator and users but also improve the wind power absorption capacity of the community and reduce the load fluctuation. •Based on the Stackelberg game, an integrated energy-pricing strategy for the community is proposed, with the operator as the leader and users as follower.•Based on the Stackelberg game relationship between the operator and users, a two-layer optimisation model is built.•Stackelberg equilibrium solution verification and model linearisation.